Highly diastereoselective synthesis of β-carboxy-γ-lactams and their ethyl esters via Sc(OTf)3-catalyzed imino Mukaiyama-aldol type reaction of 2,5-bis(trimethylsilyloxy)furan with imines - Manat Pohmakotr (2018)
(Chemical Equation Presented) Functionalized γ-lactams are found to be crucial intermediates in the synthesis of biologically important natural products. We herein described a highly diastereoselective synthesis of β-carboxy-γ-lactams and their ethyl ester derivatives, in high yields with high diastereomeric ratio, via the Mukaiyama-aldol type reaction of 2,5-bis(trimethysilyloxy)furan with imines, employing Sc(OTf)3 as a catalyst. © 2007 American Chemical Society.